Pupillometry and the vigilance decrement: Task‐evoked but not baseline pupil measures reflect declining performance in visual vigilance tasks. (18th January 2022) - Martin, Joel T.; Whittaker, Annalise H.; Johnston, Stephen J.
Abstract: Baseline and task‐evoked pupil measures are known to reflect the activity of the nervous system's central arousal mechanisms. With the increasing availability, affordability and flexibility of video‐based eye tracking hardware, these measures may one day find practical application in real‐time biobehavioural monitoring systems to assess performance or fitness for duty in tasks requiring vigilant attention. But real‐world vigilance tasks are predominantly visual in their nature and most research in this area has taken place in the auditory domain. Here, we explore the relationship between pupil size—both baseline and task‐evoked—and behavioural performance measures in two novel vigilance tasks requiring visual target detection: (1) a traditional vigilance task involving prolonged, continuous and uninterrupted performance ( n = 28) and (2) a psychomotor vigilance task ( n = 25). In both tasks, behavioural performance and task‐evoked pupil responses declined as time spent on task increased, corroborating previous reports in the literature of a vigilance decrement with a corresponding reduction in task‐evoked pupil measures. Also in line with previous findings, baseline pupil size did not show a consistent relationship with performance measures. Our data offer novel insights into the complex interplay of brain systems involved in vigilant attention and question the validity of the assumption that baseline (prestimulus) pupil size and task‐evoked (poststimulus) pupil measures reflect the tonic and phasic firing modes of the locus coeruleus. Abstract : This study explores how baseline and task‐evoked pupil measures relate to task performance in a continuous, uninterrupted vigilance task and a psychomotor vigilance task. The results show that task‐evoked pupil responses declined alongside key performance measures as time‐on‐task increased, but that baseline pupil measures did not show a clear relationship with task performance. Our data offer novel insights into the complex interplay of brain systems subserving vigilant attention.